Developing HOTS-Based Students’ Worksheet for Fifth-Grade Elementary School - Luh Gd Rahayu Budiarta (Journal of English Education and Teaching, 2021)
Higher order thinking skills (HOTS) is formulated for improving student critical thinking abilities. The aimed of this study is to develop students' worksheet based on higher-order thinking skills in learning English activities for fifth-grade elementary school students. This study used design and development (D&D) method and the ADDE models (Analysis, Design, Development, and Evaluation). The subjects were teacher and fifth-grade elementary school students. There were four topics of the worksheet were designed based on syllabus and student’s need. The students can use this worksheet to learn English by doing activities that train their critical thinking. Based on the content validity judgment, the students' worksheet was highly relevant. The quality judgment was conducted by four expert judges and 6 reviewers (1 teacher and 5 students). Based on the quality judgment, the students' worksheet was categorized as excellent media. Conclusively, the developed students' worksheet can be categorized as a learning medium that can develop students' higher-order thinking skills.